An investigation of perceptions of Prior Grammar Learning (PGL) and Current Grammar Learning (CGL) by UiTM Asasi-TESL students / Afni Anida Adnan - Adnan, Afni Anida (2008)
The decline of the standard of English in Malaysia may be deeply rooted in the preparedness of trainee teachers upon enrolling in a TESL course to study grammar extensively and explicitly. This study investigates perceptions of Prior Grammar Learning (PGL) and Current Grammar Learning (CGL) among 43 Asasi TESL students in Universiti Teknologi MARA (UiTM). The teaching and learning of grammar in universities for Pre/Asasi TESL courses is often a 14-week course of study and often, the treatment towards this subject is slightly different from the CLT approach in schools. This may lead to some challenges to Asasi TESL students as they are now required to recognize and analyze grammatical rules and learn grammar in an explicified manner. This study looks into the students' perceptions of the different requirements required of them as grammar students. The instrument used in this study is a 64 item questionnaire that looked at the students perceptions of learner anxiety, preparedness and metalinguistic knowledge and other aspects. This study reveals that out of 30 paired-sample items, 16 items showed significant changes in perceptions. These included differences in the subjects' perceptions of their ability to formulate and analyze rules. There were also significant shifts in the enjoyment and ease in learning grammar factors. All these findings revealed that there should be improvements made to the learning and teaching of grammar to better address the challenges faced by the Asasi TESL students.